2016
DOI: 10.7554/elife.18318
|View full text |Cite
|
Sign up to set email alerts
|

Folded gastrulation and T48 drive the evolution of coordinated mesoderm internalization in flies

Abstract: Gastrulation constitutes a fundamental yet diverse morphogenetic process of metazoan development. Modes of gastrulation range from stochastic translocation of individual cells to coordinated infolding of an epithelial sheet. How such morphogenetic differences are genetically encoded and whether they have provided specific developmental advantages is unclear. Here we identify two genes, folded gastrulation and t48, which in the evolution of fly gastrulation acted as a likely switch from an ingression of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 73 publications
(98 reference statements)
3
48
0
Order By: Relevance
“…In both cases, the mechanism and timing of mesoderm internalization is affected by loss of signaling, but the mesoderm is still able to internalize Zusman and Wieschaus, 1985). The same is also true for the dipteran Chironomus, where disruption of Fog signaling has a measurable impact on mesoderm internalization but the pathway is not strictly required for the process (Urbansky et al, 2016). (Handel et al, 2005).…”
Section: Fog Signaling Has Local Morphogenetic Functions During Gastrmentioning
confidence: 83%
See 4 more Smart Citations
“…In both cases, the mechanism and timing of mesoderm internalization is affected by loss of signaling, but the mesoderm is still able to internalize Zusman and Wieschaus, 1985). The same is also true for the dipteran Chironomus, where disruption of Fog signaling has a measurable impact on mesoderm internalization but the pathway is not strictly required for the process (Urbansky et al, 2016). (Handel et al, 2005).…”
Section: Fog Signaling Has Local Morphogenetic Functions During Gastrmentioning
confidence: 83%
“…The Tribolium genome contains one ortholog each for fog, mist and cta (hereafter referred to as Tc-fog, Tc-mist and Tc-cta). Fog is a fast evolving protein with very low overall sequence conservation within insects and no detectable homologs in currently available noninsect genomes (Figure 1-figure supplement 2) (Urbansky et al, 2016). In contrast, previous research has shown Mist and Cta to be well conserved among insects (de Mendoza et al, 2016;Kozasa et al, 2011;Manning et al, 2013;Parks and Wieschaus, 1991;Urbansky et al, 2016).…”
Section: Tc-cta Tc-mist and Tc-fog Are Expressed In Morphogeneticallmentioning
confidence: 92%
See 3 more Smart Citations